Entrepreneurial Leadership Influence on Competitive Adaptability in Bali Transport Industry: Case Study of Praska Trsnaport - Ananta, Fherdy Roy; Basmantra, Nyoman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This research paper examines the effect of entrepreneurial leadership to the flexibility and competitiveness of a medium size transport SME based in tourism sector in Bali. The Balinese transport industry is defined by high levels of uncertainty due to the unstable inflow of tourists, the high-speed digital destabilization, that have significantly influenced the demand of the services as well as their operational stability. Using Praska Transport as a case study, the study explains that leadership practices can help organizations to react to turbulence in the environment and maintain competitive advantage. The research has a deductive approach of qualitative case-study design. The data was collected using semi-structured interviews with the addition of direct observation and documentary analysis. According to the findings, entrepreneurial leadership that can be identified by family-oriented orientation, proactive decision making and effective use of digital technologies is a key factor that can strengthen organizational flexibility and resilience. To conclude, entrepreneurial leadership will become a strategic force of resilience and competitive flexibility to transport SMEs that tend to work in unstable tourism-related conditions providing practical recommendations to business survival and research opportunities in similar spheres.